Analisis Faktor-Faktor Yang Memengaruhi Partisipasi Pekebun Dalam Pelaksanaan Peremajaan Kelapa Sawit Di Kud Makmur - Hutabarat, Sakti; Kristin, Monika Sari; Septya, Fanny (Universitas Jambi, 2023)
Replanting is an effort to develop plantations by replacing unproductive plants with new plants. Oil palm replanting can work well if there is theparticipation of smallholders. The age of oil palm plants at KUD Makmur Lestari is no longer productive, but there are still smallholders who have not participated in replanting. This study aims to determine models and procedure for submitting an oil palm replanting program and to analyze factors that influence smallholder participation in implementing oil palm replanting program at KUD Makmur Lestari. Samples were selectedusing a purposive sampling technique with criteria of farmers who are members of KUD Makmur Lestari. The sample size used were 60 farmers. Data analysis used in this research is descriptive analysis. The results show that the replanting model used by the smallholders at KUD MakmurLestari is total cutting. The procedure for submitting BPDPKS fund starts from the farmer to the village unit cooperative (KUD) and then proceeds to PT. Ramajaya Pramukti and to the Kampar District Plantation Office. Factors that influence the participation of smallholders in implementingoil palm replanting program at KUD Makmur Lestari include age, land area, number of family dependents, farming experience, land legality, savings, and household income. This study emphasizes that the success of oil palm replanting programs is heavily influenced by farmer socioeconomic conditions, the clarity of land legality, the strength of cooperative institutions, and the effectiveness of inter-stakeholder coordination, rather than just the replanting model or the availability of funds. As a result, a comprehensive, participatory, and inclusive approach is urgently required to inspire more farmers to be daring and prepared to undertake the replanting process in a sustainable manner. Furthermore, the oil palm replanting effort is more than just a technical operation to replace old trees; it is also a strategic intervention to achieve SDGs 1, 2, 8, 12, 13, and 17.